Comparison of Very Low Birth Weight Preterm Infants with And Without Experienced Target Weight Gain on The Administration of Human Milk Fortifier - Diondra Eka Rizkiawan; Adhie Nur Radityo; Rina Pratiwi; Kusmiyati Tjahjono (Journal of Biomedicine and Translational Research, 2020)
Background: Human milk fortifier (HMF) is defined as a supplement added to breastmilk to increase calories, proteins, vitamins, and various nutrition of breastmilk. The purpose of HMF administration is to increase the concentration of breastmilk nutrients to improve the weight of very low birth weight preterm infants. The administration of HMF is insufficient to fulfill protein needs in 20-40% very low birth weight babies, thus the weight gain did not meet the expected target.Objective: To analyze characteristic differences between very low birth weight preterm infants who experienced weight gain according to the target and not according to the target on the administration of HMF.Methods: An analytical study with a case-control approach comparing case and control group, which was observed to determine characteristic differences between both groups. The samples were 52 very low birth weight preterm infants obtained by consecutive sampling. Data analysis includes descriptive analysis and hypothesis testing. Results: Data were obtained from medical records and consisted of 52 participants, including 26 very low birth weight premature infants who experienced weight gain according to the target and 26 who experienced weight gain not according to the target. There was no characteristic difference of cyanosis clinical symptoms (OR 2.3; 95% CI 0.51-10.4), chest retraction (OR 1.0; 95% CI 0.32-3.1), apnea of prematurity comorbid (OR 1.0; 95% CI 0.25-3.9), neonatal infections (OR 0.62; 95% CI 0.21-1.9), starting age of HMF administration (OR 0.62; 95% CI 0.21-1.89), bloating (OR 0.57; 95% CI 0.17-1.9), and vomiting (OR 1.18; 95% CI 0.38-3.7) in both groups.Conclusion: There was no characteristic difference between very low birth weight preterm infants who experienced weight gain according to the target and not according to the target on the administration of HMF.